Collected mass spectrometry data on monoterpene indole alkaloids from natural product chemistry research - Ramos, AEF (2019)
We gratefully acknowledge the productive collaborations and the fruitful contributions that allowed the generation of this natural products MS/MS database. This research was funded by FONDECYT-CONCYTEC (grant contract number 239-2015-FONDECYT), and by the French ANR grant (ANR-15-CE29-0001). We express our thanks to Séverine Amand (MNHN) for her assistance in the collection of the MIAs from the MNHN chemical library.